PMSM Control Simulation Based on Pumping Unit - Zikuan Zhang; Lin He (Institute of Advanced Engineering and Science, 2014)
To study direct drive pumping unit of operating state, permanent magnet synchronous motor open-loop control system was used to model and simulate based on Matlab/Simulink software, and analyzed the waveforms change with different torque. The results indicate that permanent magnet synchronous motor can operate smoothly under low speed and high torque condition, and can meet work requirement of direct drive pumping unit with acceleration. The proposed Simulink simulation system can achieve stable control in actual operation, and its effectiveness was confirmed experimentally. Results of simulation analysis have some certain practical value for pumping unit driven by permanent magnet synchronous motor. DOI : http://dx.doi.org/10.11591/telkomnika.v12i4.4836